2019
DOI: 10.7567/1882-0786/ab0c2c
|View full text |Cite
|
Sign up to set email alerts
|

Mg implantation dose dependence of MOS channel characteristics in GaN double-implanted MOSFETs

Abstract: Lateral GaN double-implanted MOSFETs (DIMOSFETs) on Mg ion implanted GaN layers with different Mg ion implantation doses have been evaluated to investigate the impact of Mg dose on MOS channel properties. It is demonstrated that the threshold voltage (Vth) and the field effect mobility (μfe) depend on the Mg dose. A maximum μfe of 173 cm2 V−1 s−1 has been obtained with a Vth of 2.2 V on the Mg implantation layer with a dose of 4.2 × 1013 cm−2. The obtained results indicate that the channel characteristics of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 26 publications
(26 reference statements)
1
41
0
Order By: Relevance
“…Although attempts have been made to realize p-GaN via Mg ion-implantation, achieving efficient p-type conductivity through this route remains a challenge. [19][20][21][22][23][24][25][26][27][28][29] The success of this route mainly depends upon finding the optimum conditions, i.e., the concentration of Mg ions, choice of protection layer, and post-implantation annealing temperature. This high-temperature annealing of the Mg-implanted GaN layers with commonly used protection layers of SiO 2 , Si 3 N 4 , and AlN removes the crystal damages induced due to ion-implantation and facilitates the migration of Mg atoms to the desired substitutional Ga sites.…”
Section: Introductionmentioning
confidence: 99%
“…Although attempts have been made to realize p-GaN via Mg ion-implantation, achieving efficient p-type conductivity through this route remains a challenge. [19][20][21][22][23][24][25][26][27][28][29] The success of this route mainly depends upon finding the optimum conditions, i.e., the concentration of Mg ions, choice of protection layer, and post-implantation annealing temperature. This high-temperature annealing of the Mg-implanted GaN layers with commonly used protection layers of SiO 2 , Si 3 N 4 , and AlN removes the crystal damages induced due to ion-implantation and facilitates the migration of Mg atoms to the desired substitutional Ga sites.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been reported that a p–n junction can be formed by Mg ion implantation by using a high‐quality free‐standing GaN substrate, and rectification characteristics and electroluminescence have been observed . In addition, the operation of a MOSFET using a Mg‐ion‐implanted layer has also been confirmed . One of the most serious problems of Mg ion implantation is the formation of V N , which cannot be repaired by postimplantation annealing.…”
Section: Introductionmentioning
confidence: 97%
“…Gallium nitride (GaN) has many unique properties such as a wide direct band gap and high thermal conductivity. GaN is used in high-temperature, high-power devices. In such applications, proper doping is necessary to prepare GaN-based MOS-FET structures where carrier control of the source, drain, and gate is crucial. In order to prepare high-quality GaN-based MOS-FET structures, the atomic structures and chemical states in active and inactive dopant sites in GaN should be clarified. Once the atomic structures and the chemical states of inactive dopant sites are clarified, we can have a strategy that vanishes or reduces the inactive sites of dopants.…”
Section: Introductionmentioning
confidence: 99%